Waste biomass pellets for green energy production - A sustainable alternative for energy security - Murtala, Namakka; Md Rezaur, Rahman; Muhammad Khusairy, Bakri (Elsevier Ltd., 2025)
Energy security remains a pressing global challenge, necessitating a transition toward sustainable renewable energy solutions. Waste biomass pellets represent a promising alternative, offering opportunities for energy diversification, carbon-neutral energy generation, and environmental sustainability. This review critically examines the production, utilization, and integration of waste biomass pellets, highlighting technological advances, process parameters, and energy conversion strategies. Key factors, including biomass feedstock type, moisture content, drying, and pelletizing conditions, strongly affect pellet quality, energy density, and storage performance. Thermochemical conversion technologies, such as co-firing, gasification, and pyrolysis, are evaluated for their efficiency, environmental impact, and operational challenges. Despite the benefits, barriers such as feedstock variability, supply chain logistics, and policy gaps hinder widespread adoption. Life cycle assessment and economic analyses indicate that biomass pellets can reduce greenhouse gas emissions at lower costs compared to conventional energy sources. The review identifies knowledge gaps, emphasizes the need for integrated technological, policy, and market strategies, and outlines future research directions to optimize biomass pellet production, enhance energy security, and support sustainable renewable energy transitions globally.